2008
DOI: 10.1007/s10384-008-0553-7
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Myxoma in a 64-year-old patient

Abstract: In addition to preservation of the number of corneal endothelial cells with the use of viscoelastic materials and changes in ultrasound power during cataract surgery, activation of the remaining endothelial cells would be benefi cial. Dexamethasone has been shown to increase the Na+,K+-ATPase activity of bovine corneal endothelial cells in vitro. 5 Topical corticosteroid administration has also proved effective for the treatment of corneal edema, possibly as a result of the activation of corneal endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It occurs equally frequently in both sexes; the ages of the patients ranged from 11 to 80 years, with a median of 50 [5, 6, 7, 8]. Chen et al [6] reported the youngest case in an 11-year-old boy; the other cases were in the range of 18–80 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It occurs equally frequently in both sexes; the ages of the patients ranged from 11 to 80 years, with a median of 50 [5, 6, 7, 8]. Chen et al [6] reported the youngest case in an 11-year-old boy; the other cases were in the range of 18–80 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…We have found only 26 cases reported in the English literature. The typical presentation of conjunctival myxoma is a painless, circumscribed, rubbery, translucent/solid, yellow-pink mass or cyst [5, 6, 7, 8]. Diseases that may resemble conjunctival myxoma include amelanotic nevus, lymphangioma, myxoid liposarcoma, spindle-cell lipoma, myxoid neurofibroma, and rhabdomyosarcoma [9].…”
Section: Introductionmentioning
confidence: 99%
“…The intracytoplasmic inclusions represent dilated cisternae of rough endoplasmic reticulum, which are theorized to have the secretory function of producing the mucoid stroma. 9,10,17 HISTOCHEMICAL AND IMMUNOHISTOCHEMICAL STUDY The conjunctiva myxoma cells stain positive for Alcian blue (Figure 4) with dissolution of the color after treatment with hyaluronidase, revealing cells that contain abundant hyaluronic acid mucopolysaccharides. 7,11,16 The cells also stain positively with mucicarmine and colloidal iron.…”
Section: Gross Pathologymentioning
confidence: 99%
“…10,11 Immunostaining of conjunctival myxoma cells show extensive reactivity with vimentin ( Figure 5) and focal staining for a-smooth muscle actin. 7,9,17 Several authors 18,19 have presented a few cases that stained negative for smooth muscle actin. In 2012, Herwig et al 14 described a variant of conjunctival myxoma that stained positive for CD34.…”
Section: Gross Pathologymentioning
confidence: 99%